An overview of cryogenic separation techniques for natural gas with high CO2 content - Lal, B. (Medwell Journals, 2018)
In the wake of an unprecedented growth of the market demand for natural gases, exploration and utilization are necessary for high impurity wells worldwide. Therefore, it has become vital to conduct research work on the development of optimized and automated processes for removal of natural gas impurities mainly CO2. Conventionally, CO2 from natural gas streams are absorbed by amine solutions or other appropriate chemical solutions but cryogenic separation technology is suitable for use if the CO2 content of the natural gas is high. In cryogenic separation, the process principle involves the separation based on the difference in volatility and desublimation. The cryogenic separation process is classified into conventional, nonconventional and hybrid techniques. Conventional process involves Liquid-Vapor (L-V) based separation. The non-conventional method includes Solid-Vapor (S-V) based separation while hybrid technique utilizes both conventional and non-conventional methods. Cryogenic research including both L-V and solid-vapor S-V based separation has recently shown several advantages and to enhance the separation performance and energy reduction, a novel concept of cryogenic hybrid (L-V and S-V) process is also discussed. Â© Medwell Journals, 2018.